Plano diretor municipal e participação popular contributiva avaliados por um modelo integrador - Colenci, Pedro Luciano (2017)
This thesis is about contributory participation in the elaboration and updating of urban planning and its goal is to demonstrate the influence of contributory management in the transformation processes which currently affect life in the cities and the Urban Planning processes. Thus, it describes the historic, political and legal development of the Brazilian urbanism; it also identifies the construction of urban law as an autonomous field of law, with the purpose of demonstrating that this field, notwithstanding it being an autonomous legal institute, it relies on political issues. It was analyzed the city democratic management and the limits of its contingency, it was carried out a diagnostic of the citizenry contribution effectiveness in the municipal public management, it was examined the participatory democracy in the city of São Carlos, in a direct way as well as in a secondary one, and, finally, it was explained the current phase of municipal planning through an integrating model. It is important to highlight that, parallel to this research, two other researches were conducted in order to accompany, collect data and evaluate the review process of the Strategic Plan of São Carlos city; as a result of this research, it is suggested a Maturity Model. Regarding the methodology, this work can be classified as a descriptive, exploratory research. As for the technique employed in the data collection, it was supported by bibliographic, documental research and the analysis of secondary data to be obtained from accomplished researches. As a research result, it was identified that the need to systematize the municipal planning activities results from the rational comprehensive model which derivate from a schematized model of decision making, which this study proposes to evaluate the Maturity Degree of the involved agents in the formation and reviewing process of the Urban Planning, with the aim of engaging the representatives and the people, in which technology and social science contributed to a better world and in which planning would be an important instrument to social progress. Therefore, participation seems as a fundamental element towards balance of the factors influencing the decision-making process.